Incorporation and analysis of LHCII in model systems - Gruszecki, Wieslaw I (Methods in molecular biology (Clifton, N.J.), 2004)
The largest light-harvesting pigment-protein complex of Photosystem II (LHCII) is an antenna complex comprising more than half of photosynthetically active chlorophyll pigments. Understanding photophysical processes in this pigment-protein complex and the relationship between the structure and function of LHCII has been the subject of numerous studies, including those in the model systems, such as monomolecular layers, Langmuir-Blodgett films, planar lipid bilayers, and liposomes. This chapter describes the methods of the incorporation of LHCII into these particular model systems, control of intactness of LHCII after incorporation, and the examination of this pigment-protein complex in model systems.